The Social and Spiritual Significance of the Jadid Movement in Turkistan (Zien Journal of Social Sciences and Humanities, 2023)
This article presents the author's general thoughts on the significance of the Jadidism movement, which played an important role in the social-philosophical, religious-ethical, and cultural development of Turkestan peoples in the second half of the 19th century and the first quarter of the 20th century. The article also mentions Turkestan jadids and their ideas